[FeFe]-Hydrogenase models assembled into vesicular structures. (March 2014) - Menzel, Kristin; Apfel, Ulf-Peter; Wolter, Nonio; Rüger, Ronny; Alpermann, Theodor; Steiniger, Frank; Gabel, Detlef; Förster, Stephan; Weigand, Wolfgang; Fahr, Alfred
Abstract Compartmentalization is a major prerequisite for the origin of life on earth according to Wächtershäuser "Iron-Sulfur-World". The hypothesis is mainly based on an autocatalytic inorganic energy reproducing redox system consisting of iron and sulfur as requirement for the subsequent synthesis of complex organic structures. Here, we modified [FeFe]-hydrogenase models by means of covalent coupling to either oleic acid or the amphiphilic block copolymer polybutadiene-polyethyleneoxide (PB-PEO) and incorporated those into the membranes of vesicles composed of phospholipids (liposomes) or the unmodified amphiphilic polymer (polymersomes). We employed a [2Fe-2S] cluster as a hydrogenase model, since these structures are known to be suitable catalysts for the generation of H2 in the presence of weak acids. Successful incorporation was confirmed by spectrophotometric iron quantification and the vesicles formed were characterized by size determination (photon correlation spectroscopy (PCS)), and zeta potential as well as by cryo-transmission electron microscopy (Cryo-TEM). The modified models could be incorporated into liposomes or polymersomes up to molar proportions of 3.15% and 28%, respectively. Due to the immobilization in vesicular bilayers the [FeFe]-hydrogenase models can even exhibit catalytic action under the particular conditions of the intravesicular microenvironment. Our results suggest that the vesicular systems described may be applied as a nanoreactor for the reduction of encapsulated substances by generating hydrogen and thus as a minimal cell model.